(3GdMeGjI GdLfGFjI dMb GdEfSGf aj MQeI GpqJUGdGJg GdTNUjI (B: s (3OQGSI ebGQfI Hjf GdbGfhfjf GdeUQj h GdCeQjcj (B/ s - (3eMeO MSGe GdOjf eMeO CMeOs; (3YeQ eMeO S``Gde (B: s ((3GdbGgQI (B: s, 2016)
(3Ef GdGJUGdGJ JYJHQ YedjI jJe NdGdgG GfJbGd eMJhi eYjf(B: (3JJe Hjf WQajf Ch CcKQ YHQ hSjdI eG(B: (3eHGTQI Ch ZjQ eHGTQI(B: (3jSJhj Cf JJe HUhQI eJRGefI Ch ZjQ eJRGefI(B. (3hjTjQ eOdhd GdMb aj MQeI GdGJUGdGJ Edi Mb GdEfSGf aj VeGf SQjI GJUGdGJg ef LGfH(B: (3hVeGf hUhdgG Edi GdZjQ ef LGfH BNQ(B. (3hJgOa GdMeGjI GdLfGFjI GdehVhYjI dMQeI GdGJUGdGJ Edi JLQje CfeGW ef GdSdhc hGdJj JeKd GYJOGA Ydi MQeI GdGJUGdGJ HCfhGYgG ShGA cGfJ TahjI(B: (3Ch SdcjI(B: (3Ch dGSdcjI(B: (3Ch EdcJQhfjI(B: (3Ch HQjOjI(B: (3Ch HQbjI(B: (3ceG JgOa GdMeGjI GdELQGFjI Edi hVY GdbhGYO GdELQGFjI GdcajdI HJMOjO BdjGJ eMOOI jecf ef NdGdgG GfJgGc MQeI GdGJUGdGJ GdTNUjI HUhQI eTQhYI hakbG debJVjGJ GdYbGH hefY GdLQjeI(B: (3hgh eG Je GSJYQGVg NdGd Jdc GdOQGSIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi (B2016s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdGJUGdGJs; (3GdMeGjI GdLfGFjIs; (3Mb GdEfSGfs; (3QSGFd LGeYjIs